Insights into exponentiation: ninth-graders’ struggles and teacher’s influence - Bihari, Gábor; Kónya, Eszter (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2023)
Our research focuses on the development of ninth-grade student’s concept of exponentiation. We conducted semi-structured interviews with four students to see to what extent they acquired the exponentiation concept by the end of the year. They had to solve four tasks, in which we could see which knowledge elements belonged to their actual level of development and which belonged to their zone of proximal development. Also, we were curious about the importance of the teacher’s role as a guide in the process of concept acquisition. That is why we analyzed the students’ and teacher’s reactions. We found several reasons why it can be challenging for students to expand their exponentiation concept to negative exponents correctly and in the long term. Also, we can state that teacher’s prompts can be determining factors in expanding a mathematical concept.